Nature and the City: Audiovisual interactions in pleasantness and psychophysiological reactions. (May 2022) - Bogdanov, V.B.; Marquis-Favre, C.; Cottet, M.; Beffara, B.; Perrin, F.; Dumortier, D.; Ellermeier, W.
Graphical abstract: Highlights: Heart rate and eyebrow muscle activity are sensitive parameters of affective sound evaluation. Pupil dilations occur in response to both unpleasant auditory or visual stimulation. Pupillary reactions are suited to indicate the presence of nature elements in both auditory and visual scenes. Pupil reaction accounts for audiovisual interactions. Nature elements in both visual and auditory scenes improve wellbeing, likely by a reduction of overall arousal level. Abstract: The presence of natural elements in the urban environment improves wellbeing. Comparisons of different psychophysiological reactions to both auditory and visual perceptions of urban environments are employed as a method for shedding light on the mechanisms involved in audiovisual interaction, by which visual context influences auditory perception, and vice versa. Combining psychophysical and physiological methodologies is likely to improve our understanding of the perceptual consequences of variations in the presence of nature in the city. In the present study, 61 participants, mainly students, were exposed to urban soundscapes accompanied by street scenes. Audio excerpts of bird song or road traffic were paired with images with or without vegetation. Half of the participants (n = 30) were asked to judge the auditory pleasantness after each audiovisual presentation, whereas the other half (n = 31) judged the visual pleasantness of the scene. Heart rate, pupil area, gaze fixations and electromyography of the eyebrow muscle ( corrugator supercilii ) were concurrently recorded. We demonstrated a strong perceptual audiovisual interaction: auditory pleasantness was higher when accompanied by a natural visual context, and visual pleasantness was higher when accompanied by natural sounds. Electromyography and heart rate were particularly sensitive to the presence of nature in the soundscapes, whereas gaze behavior discriminated only visual nature elements. The natural sounds were associated with lower heart rate and less corrugator supercilii electromyographic activity, whereas natural images were associated with slower gaze behavior. Pupil area was sensitive to both auditory and visual stimulations. The pupil was relatively constricted by all natural stimuli and discriminated different unpleasant traffic noise samples and the modulation of visual pleasantness by these sounds. This suggests a distinctive role of arousal level in the modulation of pupil reactions, which appear well suited to study audiovisual interactions and the perceptual effects of natural elements in urban environments.